Enhancing floral and habitat diversity for augmenting natural enemies in rice ecosystem of Thanjavur, Tamil Nadu, India - Nalini, R; Porpavai, S (ORYZA-An International Journal of Rice, 2019)
Field experiments on "Enhancing floral and habitat diversity for augmenting natural enemies in Thanjavur rice belt" was conducted during kharif (2017 and 2018) and rabi (2017). In habitat diversified rice crop, the main crop of rice was maintained along with flowering vegetation in field bunds viz., cowpea, green gram, black gram, sunflower, gingelly, bhendi, cluster bean, maize and marigold. Weeds mainly from Umbelliferae, Leguminosae and Compositae that support natural enemies were also maintained adjacent to rice bunds. Noncrophabitat included straw heaps on rice bunds. Daincha was planted in rogue spacing and bird perches installed to encourage both the natural enemies and insectivorous birds. The mean value of insect pest population was about 56 per cent lower in habitat diversified rice crop (7.39 insects /5 sweeps) than that of pure rice crop (16.87 insects /5 sweeps). In the case of mean value of natural enemy population, habitat diversified rice crop (26.74 individuals /5 sweeps) recorded two times higher population than that of pure rice crop (13.40 individuals /5 sweeps). In habitat diversified rice crop the pest-defender ratio was high in all the periods of observation compared to pure rice crop. The mean pest:defender ratio was 1: 3.74 in habitat diversified rice crop as compared to 1: 0.89 in pure rice crop. The mean grain yield recorded was 4.99 t/ha in habitat diversified rice crop as compared to 4.36 t/ha in pure rice crop. In habitat diversified rice crop, the per cent increased grain yield recorded over pure rice crop ranged from 10.43 to 21.18.Crop diversification and non-crop habitats certainly encouraged natural biological control by supplementing food resource and shelter. Over the years complex food web would persist leading to sustainable and ecofriendly insect pest management in rice ecosystem.